MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MEDIA MISTAR BILANGAN PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Syamsa, Denisa Nurul; Zahrah, Riza Fatimah; Febriani, Winarti Dwi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
During elementary school age children who are experiencing developments in the level of thinking definitely need a stimulus to better understand a material, one of which is in learning mathematics. Understanding of mathematical concepts is one of the most important things in the learning process, especially in the matter of addition and subtraction of integers. The purpose of this study was to improve students' learning outcomes in mathematics by using number rule media in grade 4 elementary schools in Tasikmalaya. The research method used is Classroom Action Research, data collection is done through tests, observation, documentation, interviews. The subjects in this study were 12 male students and 11 female students. The results of this study stated that learning mathematics by using a number ruler media can improve student learning outcomes. Based on the results of the pre-cycle research, cycle I and cycle II, student learning completeness in the pre-cycle reached 17.39% and experienced an increase in cycle I by 26.31% to 65.21% then in cycle II it increased again by 30.44%. to 95.65%.